EVALUATION OF A DRUG UTILIZATION PATTERN AND USE OF POTENTIALLY INAPPROPRIATE MEDICATIONS AMONG GERIATRIC PATIENTS ADMITTED TO A MEDICAL INTENSIVE CARE UNIT OF A TERTIARY CARE TEACHING HOSPITAL - PANCHAL, YASH N; VYAS, BHAVESH M; PARMAR, CHETAN G; H DUMRA, GURUSHARAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to evaluate a drug utilization pattern and use of potentially inappropriate medications (PIMs) among geriatric patients admitted to a medical intensive care unit (MICU) of a tertiary care teaching hospital. Methods: A prospective and observational study was conducted among geriatric patients admitted to a MICU of a tertiary care teaching hospital. The data relevant to study variables were collected in a pre-designed case record form. Evaluation of a drug utilization pattern was carried out using WHO core drug prescribing indicators, and the use of PIMs among patients was evaluated using the Beers criteria 2019. Results: The average duration of stay in MICU per patient was 6.98±1.82 days. Hypertension and diabetes mellitus were the two most common comorbidities found in the geriatric patients. Average 10.29±3.46 drugs were prescribed per patient. Average 0.77±0.08 antibiotics were prescribed per patient. Nearly half of the drugs were prescribed in the form of parenteral formulations. About 14.6% of the prescribed drugs were found to be potentially inappropriate according to Beer’s criteria 2019. Conclusion: The majority of the drug classes were prescribed to geriatric patients for the appropriate indications. Prescribing PIMs to geriatric patients was common. The Beers criteria have not yet found their way into mainstream clinical practice.